Physical effects of hinges shape on chainsaw felling direction in Japanese Cypress. Issue 3 (2nd September 2019) - Nagao, Makiko; Yamada, Yozo
ABSTRACT: In Japan, most felling operations are performed manually with chainsaws, owing to the steep and difficult terrain involved. The average productivity per worker is approximately 5 m 3 per day, and accident rates remain constant, with 57% of fatal accidents occurring during felling operations using chainsaws. These accidents were caused primarily by unpredictable felling direction, which typically results from unevenness of the hinge cut into the felling surface. The authors performed a pulling experiment using wires to clarify the physical function of the hinge during manual felling operations. They found that when the hinge was uneven, a moment was produced toward the thicker side of the hinge and increased as the hinge surface area increased. Consequently, a larger, uneven hinge shifts the actual felling direction away from the optimum direction.